Application of the Elements of Money Laundering Crime in Indonesian Jurisprudence - Rusianto, Rusianto; Hardyansah, Rommy; Darmawan, Didit (Metromedia, 2023)
Money laundering is a growing global problem that has a significant negative impact on the economy and financial system of a country, including Indonesia. Despite the existence of regulations that provide clear guidelines, the implementation and application of the elements of the crime of money laundering in the Indonesian legal system still faces various challenges. This study aims to analyze the application of the elements of money laundering in Indonesian jurisprudence, as well as identify the main challenges in the evidentiary process, especially in terms of demonstrating the link between the laundered funds and the original criminal act. The research also aims to evaluate the role of relevant agencies, such as PPATK, in supporting the legal process of money laundering cases and how they collaborate with other law enforcement agencies to strengthen law enforcement. With the increasing complexity of techniques used by money launderers, as well as technological limitations and inter-agency coordination, efforts to tackle money laundering require more effective strategies and better systems. This research is expected to contribute to the understanding of the application of the law in money laundering cases, as well as identify the obstacles faced in the Indonesian justice system. The results of this study are expected to provide useful recommendations for strengthening law enforcement and prevention of money laundering in Indonesia, as well as increasing the effectiveness of collaboration between relevant agencies in handling these cases.